The magic trap - Davies, Jacqueline, 1962- (Davies, Jacqueline, 1962- Lemonade war series, 2014)
Jessie and Evan are hard at work preparing to put on a professional magic show in their backyard, when their father, who has been gone for over a year, appears. They must come to terms with their own complicated feelings for their father while figuring out a way to work around the approaching storm that threatens to ruin their show. Includes a vocabulary word and definition at the start of each chapter, and instructions on how to do a card trick.